Necessity of the Needs Map in the Service Design for Smart Cities - An, Seyun; Kim, Sungwhan; Kim, Soyeon (Frontiers in Psychology, 2020)
Recently, the issue of how to involve actual service users in the service designs for Smart cities has grown in importance, as this is a key factor in determining the serviceability and sustainability of developed services. Reckless participation of users can make the service design process inefficient and cause a cost increase. So, in this study, we propose the needs map which can be applied to various stages of service development and help service designers to make efficient and reasonable decisions without being too time-consuming. The proposed needs map is a schematization of theoretical concepts for Smart city planning in accordance with the framework of service-technology-infrastructure-management (STIM). Through the needs map, various urban problems, statistical data, and users' needs in a smart city are classified and analyzed concept by concept, and these focused analysis results suggest a proper direction to researchers in the service development plan. To demonstrate experimentally the feasibility of the needs map, we applied it in practice to a service design for the Smart city experience zone located in Daejeon, South Korea.